Analysis of the potentially life threatening conditions of women in intensive care units - Monte, Alana Santos; Teles, Liana Mara Rocha; Costa, Camila Chaves da; Gomes, Linicarla Fabiole de Souza; Damasceno, Ana Kelve de Castro (Rev Rene, 2017)
Objective: to describe the main potentially life threatening conditions of women hospitalized in a maternal intensive care unit and their association with sociodemographic and obstetric variables. Methods: a cross-sectional epidemiological study was carried out with 560 women admitted to an Intensive Care Unit. Results: the most prevalent conditions were: use of blood products and severe preeclampsia/eclampsia. There was a statistical association between women from the metropolitan region, in the age group of 20 to 34 years and who had previously given birth. Mothers who had a potentially life threatening condition presented a higher chance of having a child with Apgar